Participatory process training over Skype for Ethiopian enumerators in Amhara and Tigray regions - Osgood, Daniel; Diro, Rahel (2019)
The Financial Instruments Services Team at the International Research Institute for Climate and Society at Columbia University developed a prototype database for and collected extensive crowdsourced farmer drought experience data using participatory processes and Interactive Voice Response in 10 countries in Africa and Asia (Ethiopia, Senegal, The Gambia, Malawi, Zambia, Zimbabwe, Mozambique, Madagascar, Pakistan, Bangladesh). The data collection reached ~6,000 farmers.